First observation of the decay of the 13/2+ isomer in 183Hg and B(M2) systematics of neutron transitions across the nuclear chart - H. Huang; W.Q. Zhang; A.N. Andreyev; Z. Liu; D. Seweryniak; Z.H. Li; C.Y. Guo; A.E. Barzakh; P. Van Duppen; B. Andel; S. Antalic; M. Block; et al. (Physics Letters B, 2022)
The decay of the 13/2+ isomeric state in 183Hg was observed for the first time following the α decay of the 13/2+ isomer in 187Pb produced in the 142Nd(50Cr, 2p3n) reaction. Using α−γ delayed coincidence measurements, the half-life of this isomer was measured to be 290(30) μs. This isomer is proposed to deexcite by an unobserved low-energy M2 transition to the known 9/2− member of a strongly prolate-deformed 7/2−[514] band, followed by a 105-keV M1 transition to the bandhead. A lower limit of B(M2) ≥ 0.018 W.u. was deduced for the unobserved transition. The presumed retardation is proposed to be due to the notable shape change between the initial, nearly spherical, and the final, strongly deformed, states. A similar scenario is also considered for the 13/2+ isomer in 181Hg, suggesting both are cases of shape isomers. The B(M2) systematics of neutron transitions across the nuclear chart is discussed.